A comprehensive review of risks and mitigation strategies for safe hydrogen infrastructure deployment - Mensah, Rhoda Afriyie; Correa, Andrea; Asante-Okyere, Solomon; Wallmark, Cecilia; Försth, Michael (Frontiers in Chemical Engineering, 2026)
As hydrogen gains momentum as a clean and versatile energy carrier for decarbonizing hard-to-abate sectors, ensuring the safety of hydrogen infrastructure becomes critical for its widespread adoption. This review draws on peer-reviewed literature, industrial reports, and international standards for hydrogen technologies. It systematically examines safety risks across the hydrogen value chain, from production to end-of-life and assesses the effectiveness of existing mitigation strategies as well as identifying key research gaps. Common risks such as hydrogen leaks, over-pressurization, and material degradation are present at nearly every stage. Less frequent but potentially severe hazards include the risk of ice formation or equipment damage from cryogenic hydrogen leaks, and toxic exposures from chemical carriers like ammonia or hydrides used for hydrogen storage and transport. The mitigation technologies evaluated include leak detection systems, quick-release valves, emergency ventilation, and both material-based and physical barrier systems. While these safety solutions provide considerable protective potential, their long-term effectiveness depends on real-time responsiveness, and regulatory enforcement. The review also highlights critical gaps in predictive modeling, material durability under extreme conditions exacerbated by climate change, and human error analysis. Emerging technologies, such as AI-enabled safety systems and digital twins, remain underexplored, and current hydrogen safety frameworks have a limited understanding of hydrogen combustion behavior and effective fire suppression strategies. To support the safe and scalable deployment of hydrogen infrastructure, the study calls for targeted research, stakeholder education, and harmonized safety standards. This review provides a timely synthesis of risks and controls to guide future development, policy, and innovation in hydrogen safety. This review will support industry stakeholders, and researchers in developing safer, more reliable, and standardized hydrogen infrastructure.